Degree of twist in the Achilles tendon interacts with its length and thickness in affecting local strain magnitude: a finite element analysis - Enomoto, Shota; Furuuchi, Shunya; Ishibashi, Tatsuki; Yamada, Shu; Oda, Toshiaki (Frontiers in Bioengineering and Biotechnology, 2024)
The relationship between the twisting of the three subtendons of the Achilles tendon (AT) and local strain has received attention in recent years. The present study aimed to elucidate how the degree of twist in the AT affects strain using finite element (FE) analysis, while also considering other geometries (e.g., length, thickness, and width) and their combinations. Methods: A total of 59 FE models with different degrees of twist and geometries were created. A lengthening force (z-axis) of 1,000 N was applied to each subtendon (total: 3,000 N). The average value of the first principal Lagrange strain was calculated for the middle third of the total length of the model. Results: Statistical (stepwise) analysis revealed the effects of the degree of twist, other geometries, and their combinations on AT strain. The main findings were as follows: (1) a greater degree of twist resulted in higher average strains (t = 9.28, P < 0.0001) and ( 2) the effect of the degree of twist on the strain depended on dimensions of thickness of the most distal part of the AT (t = -4.49, P < 0.0001) and the length of the AT (t = -3.82, P = 0.0005). Specifically, when the thickness of the most distal part and length were large, the degree of twist had a small effect on the first principal Lagrange strain; however, when the thickness of the most distal part and length were small, a greater degree of twist results in higher first principal Lagrange strain. Conclusion: These results indicate that the relationship between the degree of twist and local strain is complex and may not be accurately assessed by FE simulation using a single geometry.